The predicting factors of bisphosphonate-related osteonecrosis of the jaw - Chafai , Ghizlane (2017)
Osteonecrosis of the jaw (ONJ) is a main adverse effect related to Bisphosphonates (BPs). Bisphosphonates are potent inhibitors of bone resorption and are most widely prescribed drugs for the treatment of osteoporosis, and are also used in malignant bone metastases, multiple myeloma, and Paget’s disease. With increasing use, evidence is emerging that patients taking BPs are at risk of developing bisphosphonate related-osteonecrosis of the jaw (BRONJ), sometimes occurring spontaneously, but more commonly following dental extractions or oral bone surgery. However, the pathogenesis of BRONJ remains unknown. Attempts have been made to predict the development of BRONJ. The aim of this study is to review and to discuss if the biomarkers and the systematic markers of bone turnover can be used to predict the risk of BRONJ. The methodology used in the accomplishment of this work was based on a bibliographic review for the subject under study.